An Investigation into Factors Demotivating Students in EFL Learning at Tertiary Level - Tuyen, Le Van; Cat Tien, Dang Ngoc (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Nowadays in Vietnam English is a compulsory subject for all students at tertiary level. Students are required to be able to use the language well after graduation. However, it is not really easy for all of them to meet the requirements and expectations of both institutions and society. Although most of them may be motivated in learning English, many factors may affect their learning. The major aim of this study was to investigate the factors that demotivate the students in learning English as a foreign language (EFL) at a private university in Da LatCity-Vietnam (Henceforth called PUD). It also attempted to explore what strategies might be adopted to overcome demotivating factors in the English classroom.200 non-English majored students of PUD participated in the study. Both qualitative and quantitative data was collected for the study. The research instruments employed for collecting data were the questionnaire and interview. For analyzing the collected data, content analysis, factor analysis and descriptive statistics were used. The findings of the study revealed that among teacher-related, classroom-related, and student-related factors, the student-related factors affected the students the most. Furthermore, the findings of this study explored the students’ perspectives of several strategies which might be used in classto help both students and teachers reduce demotivating factors in EFL learning.